Optimization of Cream Formula Extract Sargassum Crassifolium Using Varied Concentrations of Glyceryl Monostearate and Triethanolamine Emulgators With The Simplex Lattice Design Method - Utari, Weny Syafitri; Pratiwi, Eskarani Tri; Subaidah, Windah Anugrah; Ridwan, Sucilawaty (Jurnal Biologi Tropis, 2025)
Sargassum sp. contains bioactive compounds in the form of phenols that have the potential as sunscreen agents in the ultra category, namely 33.2 ± 3.11. The most commonly used formulation for sunscreen products is cream. The purpose of this study was to determine the optimal concentration of glyceryl monostearate and triethanolamine as emulsifiers for Sargassum sp. extract cream, as well as to investigate the physical properties of the optimal Sargassum sp. extract cream formulation. Optimization of the cream formulation was carried out using the Simplex Lattice Design method with Design Expert 13 software, resulting in 8 formulations. The optimal formula obtained was then subjected to physical evaluation, including organoleptic evaluation, homogeneity, and emulsion type. Data analysis used the one-sample t-test method in SPSS version 25. The yield of Sargassum sp. extract was 7.37%. The optimization results showed that the optimal concentration was 7.6% glyceryl monostearate and 0.5% triethanolamine. The optimal cream formulation has good physical properties, namely a soft semi-solid texture, light green color, homogeneity, oil-in-water cream type, pH value of 7.64±0.03, viscosity of 7.626±261.02 cP, adhesive power of 4.37±0.06 seconds, and spreadability of 6.3±0.11 cm. The results of the one-sample t-test statistical analysis of the physical properties of the optimal formulation showed no significant difference from the predicted results, with a confidence level (p>0.05).